The Development of Murabaha in Indonesian Islamic Banks - Ari Kurniawan; Abd Shomad (Universitas Muhammadiyah Sidoarjo, 2016)
Over the last few years, Islamic trading transaction has become more popular in Indonesia. Retail trade in Islamic banks for an example. There are many Islamic banks in Indonesia that provide alternative business transactions and halal product in retail trade to the public based on Islamic law, but Islamic banks must obey not only the origins of Islamic law, such as the Holy Qur’an and the Sunnah but also Islamic principle in terms of the prohibition of uncertainty, interest and gambling when they run their business in retail trade. One of the agreements in retail trade is Murabaha which involves several possible structures, notably direct trading, company (seller) purchases via an agent or a third party and murabaha via the customer as an Agent. However, there are several contemporary issues, particularly Murabaha via Shares and executing time of Murabaha that still need to be discussed whether they disobey Islamic law and basic Islamic principles or not.